Comparative Evaluation of Antioxidant and Antibacterial Activities of Helichrysum plicatum Obtained by Different Extraction Methods, with Phenolic Profiling by LC-MS/MS - Yıldırım, Aybeniz; Gül, A.kadir (My University, 2025)
This study aimed to perform a comparative evaluation of the antioxidant and antibacterial properties of ethanol-based extracts obtained using different extraction methods (microwave, ultrasonic, and maceration) of Helichrysum plicatum DC. In this context, total phenol content (TPC), total flavonoid content (TFC), and antioxidant activity of the extracts were determined. Furthermore, the antibacterial activity of the extracts was investigated using human pathogenic strains of Escherichia coli, Enterococcus faecalis, Staphylococcus aureus, and Pseudomonas aeruginosa. The types of phenolic compounds in the most effective microwave extract were identified using liquid chromatography tandem mass spectrometry (LC-MS/MS). The DPPH (2,2-diphenyl-1-picrylhydrazyl) radical scavenging assay was used to assess the extracts' antioxidant performance. Among the tested samples, the microwave-assisted extract exhibited the strongest activity, with an IC50 value of 86.40 µg/mL. In addition, TPC and TFC analyses revealed that the microwave extract contained the highest levels of bioactive compounds, with 484.99 mg GAE/g extract and 292.50 mg QE/g extract, respectively. As a result of antibacterial activity tests, it was determined that the microwave extract showed the highest effect against the S. aureus strain by forming an inhibition zone of 20.60 mm. On the other hand, maceration extract exhibited an inhibition zone of 18.60 mm in diameter in the same bacterial strain. LC-MS/MS analysis revealed that quercetin (54.84 µg/g), trans-ferulic acid (23.38 µg/g), and salicylic acid (5.24 µg/g) were the major phenolic compounds in the microwave extract. These findings reveal the potential of H. plicatum extracts as natural antioxidants and antibacterial agents, and demonstrate the superiority of microwave extraction in terms of phenolic and flavonoid compound yield as well as biological activity.
Keywords: Helichrysum plicatum; Antioxidant activity; Antibacterial activity; Phenolic compounds; LC-MS/MS analysis